Disentangling the importance of social and ecological information in goal-directed movements in a wild primate. (March 2021) - de Guinea, Miguel; Estrada, Alejandro; Janmaat, Karline R.M.; Nekaris, K. Anne-Isola; Van Belle, Sarie
Abstract : Memories linked to specific locations provide information for animals to plan future actions and anticipate the occurrence of events. Here, we examined goal-directed travel towards locations where biologically meaningful events had previously taken place to elucidate the relative importance of past social and ecological information for route planning. We inferred goal-directed travelling by detecting long sections of straight-line travel, followed by significant directional changes along travel trajectories of five neighbouring groups of black howler monkeys, Alouatta pigra, at Palenque National Park, Mexico. Post hoc, we determined at the approached locations: (1) the behaviour of the group; (2) the occurrence of previous intergroup interactions; and (3) the ecological properties of the feeding tree (i.e. importance in diet, level of phenological synchrony). The likelihood of goal-directed travel towards a location to engage in loud calling increased after having experienced an encounter with a neighbouring group at that same location in the past. Additionally, the likelihood of goal-directed travel towards a location to forage on fruits increased when the approached tree was considered important in the diet with highly synchronous phenological cycles. Our results indicate that route planning in wild animals involves an integration of both social and ecological variables. Highlights: We examined the effect of past social and ecological events on movement decisions. Goal-directed movement occurred towards locations where encounters had taken place. Phenologically synchronous, fruit-bearing trees attracted goal-directed travel. We provide novel evidence supporting planning skills in wild primates.